Genetic variability of horseshoe crab, tachypleus gigas (muller) populations from Tanjung Dawai, Kedah and Cherating, Pahang - Shazani Sarijan (Fakulti Sains dan Teknologi, 2012)
In Malaysia, horseshoe crabs, Tachypleus gigas (Muller) have been investigated for their abundance and morphology but very little information on their population size and phytogeny. This study was conducted to investigate the genetic variability and structure of two Malaysian T. gigas populations: Cherating, Pahang and Tanjung Dawai, Kedah. Random amplified polymorphic DNA (RAPD) and 18S rRNA gene sequence analyses were utilized to determine polymorphisms in these populations.